Hydroxymethylnitrofurazone lymphatic uptake with nanostructured lipid carrier after oral administration in rats - de Souza, Aline (2024)
Background: Leishmaniasis, caused by the protozoan Leishmania sp., infects phagocyte cells present in lymphatic organs. This study demonstrates the influence of nanostructured lipid carrier-loaded hydroxymethylnitrofurazone (NLC-NFOH) on lymphatic uptake using a chylomicron-blocking flow model in rats. Method: Lymphatic uptake of NFOH was assessed 1 h after oral administration of dimethyl sulfoxide with NFOH or NLC-NFOH with and without cycloheximide pretreatment. Result: Dimethyl sulfoxide with NFOH and NLC-NFOH showed NFOH serum concentrations of 0.0316 and 0.0291 μg/ml, respectively. After chylomicron blocking, NFOH was not detected. Conclusion: Despite log P below 5, NFOH was successfully taken up by the lymphatic system. Long-chain fatty acids and particle size might be main factors in these findings. NLC-NFOH is a promising and convenient platform for treating leishmaniasis via oral administration.